2012
DOI: 10.1007/s10886-012-0088-8
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Synthetic Odorant Blend for Trapping of Malaria and Other African Mosquito Species

Abstract: Estimating the biting fraction of mosquitoes is of critical importance for risk assessment of malaria transmission. Here, we present a novel odor-based tool that has been rigorously assessed in semi-field assays and traditional African villages for estimating the number of mosquitoes that enter houses in search of a blood meal. A standard synthetic blend (SB) consisting of ammonia, (S)-lactic acid, tetradecanoic acid, and carbon dioxide was complemented with isovaleric acid, 4,5 dimethylthiazole, 2-methyl-1-bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
165
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(174 citation statements)
references
References 41 publications
9
165
0
Order By: Relevance
“…• 10 E). For the rearing and maintenance of spiders in the laboratory, we followed procedures that are standard for our salticid research (see: [25]) and summarize only essential details here.…”
Section: Psychementioning
confidence: 99%
“…• 10 E). For the rearing and maintenance of spiders in the laboratory, we followed procedures that are standard for our salticid research (see: [25]) and summarize only essential details here.…”
Section: Psychementioning
confidence: 99%
“…[94,95]. Several approaches are currently available for oral delivery to mosquitoes by droplet or liquid feeding, through dry diets [96], or via nylon strips continuously dispensing synthetic mosquito attractants for several weeks [97,98]. Some of these methods have been already used to deliver to dipterans lipid-based [99] and chitosan nanoparticles [100].…”
Section: Direct Antimalarial Drug Administration To Mosquitoesmentioning
confidence: 99%
“…Studies to characterise the components of human odour which are attractive to hostseeking Anopheles gambiae s.s. have led to the identification of a large number of compounds (Mukabana et al, 2012b;Okumu et al, 2010b;Verhulst et al, 2011b) which, at appropriate concentrations, can be combined to create synthetic mosquito lures that mimic a human host (Menger et al, 2014b;Okumu et al, 2010b). These lures can remain attractive to mosquitoes even after a year of use .…”
Section: This Thesismentioning
confidence: 99%
“…The number of mosquitoes relative to humans and the mosquito survival rate depend on several aspects; in the first case the relative attractiveness of the OBT compared to a human (Okumu et al, 2010a;Okumu et al, 2010c). The blend [MB5] of attractants used in this intervention (Mukabana et al, 2012b;Verhulst et al, 2009) was reported to be more attractive than a human odour (Okumu et al, 2010b), however, the same level of efficacy is yet to be confirmed in field settings. Besides, there is some uncertainty about whether mosquitoes tend to directly prefer the trap over a human.…”
Section: Eir =mentioning
confidence: 99%
See 1 more Smart Citation